2019
DOI: 10.17826/cumj.493360
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer worry and factors affecting healthy lifestyle behaviors among women aged 15-49

Abstract: This study was conducted in order to determine the breast cancer worry of women in 15-49 aged and the factors that affect their healthy lifestyle behaviors. Materials and Methods: This descriptive research, which was conducted with 425 women who were registered in the Family Health Center in a province located in Kahramanmaraş. The data of the research were obtained by using Personal Information Form, Breast Cancer Worry Scale and Healthy Lifestyle Behaviors Scale II. Results: Total score averages of women fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
6
Order By: Relevance
“…14 8 Gözüyeşil ve arkadaşlarının çalışmasında da kadınların MKES toplam puan ortalamasının 8,60±5,1 ve %69,6'sının kanser endişesi düşük düzeyde olduğu saptanmıştır. 9 Murphy ve arkadaşlarının çalışmasında orta ve düşük düzeyde meme kanserine yakalanma endişesinin katılımcıların %57'sinde var olduğu saptanmıştır. 16 Literatüre ters yönde bulduğumuz hemşirelerin yarıdan fazlasının yüksek düzeyde meme kanseri endişesi taşımasının, onların sağlık konusunda bilgi düzeyinin bu endişeyi veya farkındalığı arttırdığı düşünülmüştür.…”
Section: Tanımlayıcı öZellikler Formuunclassified
See 3 more Smart Citations
“…14 8 Gözüyeşil ve arkadaşlarının çalışmasında da kadınların MKES toplam puan ortalamasının 8,60±5,1 ve %69,6'sının kanser endişesi düşük düzeyde olduğu saptanmıştır. 9 Murphy ve arkadaşlarının çalışmasında orta ve düşük düzeyde meme kanserine yakalanma endişesinin katılımcıların %57'sinde var olduğu saptanmıştır. 16 Literatüre ters yönde bulduğumuz hemşirelerin yarıdan fazlasının yüksek düzeyde meme kanseri endişesi taşımasının, onların sağlık konusunda bilgi düzeyinin bu endişeyi veya farkındalığı arttırdığı düşünülmüştür.…”
Section: Tanımlayıcı öZellikler Formuunclassified
“…Gözüyeşil ve arkadaşlarının çalışmasında da düzenli KKMM yapan kadınların meme kanseri endişelerinin daha fazla olduğu saptanmıştır. 9 Nacar'ın çalışmasında ise klinik meme muayenesi yaptıranların, klinik meme muayenesi yaptırmayanlara göre 0,4 kat daha fazla meme kanseri endişesi taşıdığı saptanmıştır. 8 Meme kanserine yakalanma konusunda belirli düzeyde endişe yaşamanın koruyucu davranışları uygulamaya yönelik teşvik edici olabileceği ancak endişe düzeyinin aşırı yükselmesinin ise kadınlar için danışmanlığı gerektireceği düşünülmüştür.…”
Section: Meme Kanseri Endişe öLçeğiunclassified
See 2 more Smart Citations
“…In our study, the mean score of the Healthy Lifestyle Behaviors Scale II was found to be 130.46 ± 29.16. In a study conducted in a Turkish sample before the pandemic, it was found to be 142.73 ± 26.3 [ 38 ], and 126.8 ± 19.2 [ 39 ] in another study. According to these results, we can say that the healthy lifestyle behavior levels of women in the pre-pandemic and pandemic period are similar.…”
Section: Discussionmentioning
confidence: 99%